The effects of phosphatidic acid supplementation on strength, body composition, muscular endurance, power, agility, and vertical jump in resistance trained men - Escalante, G.; Alencar, M.; Haddock, B.; Harvey, P. (Journal of the International Society of Sports Nutrition, 2016)
Phosphatidic acid (PA) is a lipid messenger that has been shown to increase muscle protein synthesis via signaling stimulation of the mammalian target of rapamycin (mTOR). MaxxTOR® (MT) is a supplement that contains PA as the main active ingredient but also contains other synergistic mTOR signaling substances including L-Leucine, Beta-Hydroxy-Beta-Methylbutyrate (HMB), and Vitamin D3.